Down-regulation of activated factor XIII by polymorphonuclear granulocyte proteases within fibrin clot - Bagoly, Zsuzsa; Haramura, Gizella; Muszbek, László (Thrombosis and Haemostasis, 2007)
Activated clotting factors are down-regulated by two major mechanisms which involve protease inhibitors or proteolytic degradation. To date, no down-regulating mechanism for activated factor XIII (FXIIIa) has been demonstrated. As the hemostatic plug contains polymorphonuclear granulocytes (PMNs) rich in proteolytic enzymes, we tested if these proteases are released in fibrin clots, and become involved in the down-regulation of FXIIIa.The supernatant of stimulated granulocytes proteolytically degraded and inactivated FXIIIa. In the fibrin clot formed from fibrinogen solution elastase, cathepsin G and matrix metalloprotease-9 (MMP-9) were released from granulocytes without any external stimulus. PMN proteases released in fibrin clot exerted a fibrinolytic effect and almost completely de-graded both FXIII subunits.The elastase inhibitor, ONO 5046, partially inhibited the proteolytic degradation of FXIII in PMNsupplemented fibrin clots. Cathepsin G and MMP-9 inhibitors provided less protection; in these cases intermediate split products accumulated.The proteolytic degradation of FXIII by PMNs was also significant when the clot was made from whole plasma. The main plasma protease inhibitor, α1-antitrypsin, provided only partial protection. In the fibrin clot which contained α1-antitrypsin FXIIIa was degraded by PMN proteases significantly faster than cross-linked fibrin.The results suggest that the degradation of FXIII subunits by the concerted action of PMN proteases released within the clot represents a novel mechanism for the down-regulation of FXIIIa.
Keywords: Elastase; factor XIII; fibrinogen; fibrin; polymorphonuclear granulocytes